Potential of Platinum Standard Reference Genomes to Exploit Natural Variation in the Wild Relatives of Rice - Mussurova, Saule; Al-Bader, Noor; Zuccolo, Andrea; Wing, Rod A. (Frontiers in Plant Science, 2020)
As the world’s population expands to 10 billion over the next 30 years, scientists and farmers across the globe must explore every angle necessary to provide a safe, stable, and sustainable food supply for generations to come. Rice, and its wild relatives (WRs) in the genus Oryza, will play a significant role in helping to solve this question due to its place as a staple food for billions. The genus Oryza is composed of 27 species that span 15 million years of evolutionary diversification and have been shown to contain a plethora of untapped adaptive traits, e.g. biotic/abiotic resistances, which can be used to improve cultivated rice. Such traits can be introduced into cultivated rice, in some cases by conventional crossing, and others via genetic transformation and gene editing methods. In cases where traits are too complex to easily transfer to cultivated rice (e.g. quantitative trait loci (QTL)), an alternative strategy is to domesticate the WR that already contains the desired adaptive traist(s) – “neodomestication”. To utilize the Oryza genus for crop improvement and neodomestication, we first need a set of genomic resources that can be used to efficiently identify, capture and guide molecular crop improvement. Here we introduce the concept of platinum standard reference genome sequences (PSRefSeq) – a new standard by which contiguous near-gap free reference genomes can now be produced. By having a set of PSRefSeqs for every Oryza species we set a new bar for how crop WRs can be integrated into crop improvement programs.